KURIKULUM RESPONSIF: MEMFASILITASI KERAGAMAN PESERTA DIDIK SEKOLAH DASAR MELALUI PENDEKATAN PEMBELAJARAN BERDIFERENSIASI - NUR UMMI AFIFAH; Nuhyal Ulia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Implementing a responsive curriculum in elementary schools is increasingly important in facing the growing diversity of students. This article aims to explore how a differentiated learning approach can facilitate such diversity, as well as improve students' learning experiences. The method used is Systematic Literature Review (SLR) to collect and analyze the latest research regarding the application of differentiated learning in the context of a responsive curriculum. The research results show that differentiated learning allows teachers to adapt teaching methods to the unique characteristics of each learner, thereby encouraging student engagement and motivation. Apart from that, this approach also contributes to the development of social and emotional skills, as well as students' creativity. Differentiated learning gives students choice in how they learn, which increases their sense of ownership in the educational process. This research also identified various challenges faced by teachers in implementing this approach, such as the need for adequate training and resources. The conclusion of this research confirms that implementing a responsive curriculum through differentiated learning not only meets students' academic needs, but also supports the holistic development of individual character and potential. This strategy is a strategic step in realizing inclusive and high-quality education at the elementary school level, which prepares students to face challenges in a diverse society.